Missed opportunities: are residents prepared to care for transgender patients? A study of family medicine, psychiatry, endocrinology, and urology residents - Coutin, Alexandre; Wright, Sarah; Li, Christine; Fung, Raymond (Canadian Medical Education Journal, 2018)
Background: The transgender (trans) population faces multiple barriers in accessing health care, with knowledge deficits of health care providers contributing substantially. Trans patients report having to teach health care professionals about their own health needs.We compared perceptions of trans-care education and training across family medicine, psychiatry, endocrinology, and urology residency training programs at the University of Toronto. Methods: We surveyed residents to assess their perceptions of and attitudes towards trans-care, exposure to trans patients, knowledge of trans-specific clinical care, and the state of trans-care education within their training. We used Likert scale data to identify patterns across residency programs. We collected open-ended responses to further explain quantitative findings where appropriate. Results: Of 556 residents approached, 319 participated (response rate = 57.4%). Nearly all endocrinology and psychiatry residents agreed that trans-care falls within their scope of practice, while only 71% and 50% of family medicine and urology residents did, respectively. Though participants were at different stages of their postgraduate training when surveyed, only 17% of all participants predicted they would feel competent to provide specialty-specific trans-care by the end of their residency and only 12% felt that their training was adequate to care for this population. Conclusion: Though the study revealed a willingness to serve this population, there was a lack of clinical exposure and trans-related teaching within postgraduate curricula resulting in feelings of unpreparedness to meet the health care needs of this underserved population.